Iddah in a Philosophical, Normative. Juridical, Psychological, Sociological, and Economic Perpective - Yusmita (Islamic Research Publiser, 2022)
Iddah has relevance to human life, including psychological, sociological, economic, and philosophical. The method used in this research is a descriptive-analytical method, with the primary approach being normative juridical. The Review of some of these elements includes: a review of the philosophy of iddah is to see the cleanliness of a wife's womb so that there is no mixing of seeds between two people. This aims to clarify the lineage of a child. Normative and juridical reviews of iddah have been regulated in the Qur'an, Hadith, and the Compilation of Islamic Law. The psychological Review of the iddah period gives the husband time to consider his household, whether it will be disbanded forever or rebuilt by preparing a stronger mentality to build a better household. Sociological Review, women are limited in socializing with people outside the home, especially with men who are not mahram. Meanwhile, from an economic perspective, a woman in the iddah has the right to earn a living from her husband. He is also entitled to a decent place to live. The husband is obliged to settle pending dowry cases or other obligations related to the economy, such as childcare costs, expenses during pregnancy, and expenses needed in daily life